Black Bodies in Diverse Cities - Muthoni, Ndirangu Maureen; Kgaugelo, Lekalakala; Masere, Oriaro Ibrahim Damianus (MAJ - Malaysia Architectural Journal, 2025)
Diversity in the human composition of cities can be a resource in the development of a diverse city in the future mega city. To be able to achieve diversity in our cities, both systems and the spatial environment need to allow for social inclusion of people of different cultures, races, religion, demographics, among others. The world over, cross-border migration has become very popular as people travel for leisure, work, study, opportunities, as refugees, seeking asylum, among others. However, the black body has always been positioned in a state of immobilization and displacement especially in Western cities. These problems include the circumvention of procedures and design of hostile spaces all aimed at deterring them from travel, access to their destinations, safety, and comfort in their destinations. For instance, some transport hubs such as airports are used as a weapon or barrier to filter which blacks are welcomed or not. Moreover, the built fabric promotes unequal access to facilities e.g., elite establishments, unequal treatment, and security checks in comparison to fellow white travellers. The likely result is architecture being used as a tool to mitigate and support spaces of displacement, imprisonment, and unintegrated planning from the urban scale to the cold concrete finishes that ensure one is uncomfortable and unwelcomed when detained or assessed. In summary, this paper seeks to spark a conversation based on aforementioned factors that have led to marginalisation of certain groups of people in cities’ transit hubs, to the detriment of their heritage. Further, proposed solutions towards achieving culturally diverse cities through design will be explored through the role of architecture as an agent to minimize exclusion, create inclusive transit spaces and positive intercultural encounters and exchanges without perceiving certain cultures or races as superior to others.